Exploring the Efficacy and Feasibility of Wind Energy as A Panacea for Eskom’s Sustainable Generation with Energy Security and Energy Poverty - Maleka, Victor Chipane; Islam, Mohammad Shahidul (European Journal of Applied Sciences, 2023)
There is ample proof that South Africa's ongoing reliance on fossil fuels as its primary source of energy consumption. It has contributed to the release of greenhouse gases that have exacerbated ecosystem disruption causing global warming and climate change. The study investigated and evaluated the effectiveness and feasibility of wind energy as a magic bullet to improve energy security, sustainable energy production, and alleviate energy poverty in South Africa. This is in order to improve sustainable energy generation, energy security, and the elimination of these problems. A thorough literature review of papers published between 2015 and 2022 was done in this study. SWOT analysis method (strengths, weaknesses, opportunities, and threats) is also used in the study. According to the analysis, Eskom's deployment of wind energy at a large scale can enhance South Africa's energy security and sustainably provide power while also lowering the country's present level of energy poverty. The systematic literature review indicates that South Africa, particularly in the Eastern and Western Cape regions, offers significant potential for and capacity for renewable wind energy. In order to incorporate renewable sources into its energy mix and achieve energy sustainability, Eskom should use macro-level strategies that discourage carbon-based energy.